Literatur Review Faktor-Faktor yang Mempengaruhi Kejadian Bayi Berat Lahir Rendah (BBLR) - Fathmah Nurul Aslamiah; Lusiana Tandi Limbong; Marisa Margareta; Putri Astria Dewi; Yulianti Tasik; Kartika Sari (Universitas Ngudi Waluyo, 2024)
Low Birth Weight (LBW) is one of the leading causes of neonatal morbidity and mortality worldwide, especially in developing countries. The factors influencing LBW include maternal health, environmental exposure, nutritional status, and access to healthcare services. This study aims to identify the factors associated with LBW through a literature review of six recent studies from the last five years. The method used is a systematic literature search through PubMed, Google Scholar, and ScienceDirect databases using keywords: